The Lexicographic Treatment of Neuter Indefinite Quantifiers in Spanish: the Case of algo - Arar, Tariq Emad Ibrahim; Al ewaidat, Ali Saleh Sahoum; Al Areed, Rasha; Al-Oliemat, Ahmed Sulieman; Abdelmontaleb, Saber Mahmoud (Journal of Ecohumanism, 2025)
It is known that indefinite quantifiers constitute a major component in the current Spanish language, mainly DUE to its special uses and colloquial expressions of which they are a part. It is about studying in detail the case of the quantifier algo in two Spanish dictionaries, focusing on the semantic and grammatical aspects. We have consulted the corpora: Corpora del Español: Web/dialects to complete the study and check each use and expression mentioned in the dictionaries and to search for other current uses that are not included in both dictionaries. Therefore, we have observed a good number of missing uses and expressions, which implies that the study serves to cover these deficiencies and to solve the difficulties that may arise in the field of language teaching when dealing with the quantifier algo.